Fear and Fear Memory. Issue 2 (September 2016) - Pape, Hans‐Christian
Abstract: It's a worrying fact that one in five people will experience an anxiety disorder at some point in their lives. This makes it all the more important to understand the cellular basis and molecular mechanisms of these emotions. Neurophysiology research is providing some illuminating answers.